1985
DOI: 10.1007/bf01868744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anions on cellular volume and transepithelial Na+ transport across toad urinary bladder

Abstract: The effects of complete substitution of gluconate for mucosal and/or serosal medium Cl- on transepithelial Na+ transport have been studied using toad urinary bladder. With mucosal gluconate, transepithelial potential difference (VT) decreased rapidly, transepithelial resistance (RT) increased, and calculated short-circuit current (Isc) decreased. Calculated ENa was unaffected, indicating that the inhibition of Na+ transport was a consequence of a decreased apical membrane Na+ conductance. This conclusion was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 45 publications
8
30
0
Order By: Relevance
“…Although short-circuited bladders bathed in normal gluconate Ringer solution modified their transepithelial currents when challenged with an osmotic step, we have not located a consistent lower limit of osmolality of the serosal bathing medium beyond which short-circuit current would be unaffected by hypo-osmotic steps. However, as reported by others (Lewis et al 1985), a bladder bathed on the serosal side by a gluconate Ringer solution in which sodium gluconate concentration was reduced by 50 %, produced a current approximately equal to that generated by the same bladder when bathed by a normal chloride Ringer solution. Hypo-osmotic steps in this diluted gluconate medium had little further effect on the SCC, indicating that a limit had been reached or passed.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Although short-circuited bladders bathed in normal gluconate Ringer solution modified their transepithelial currents when challenged with an osmotic step, we have not located a consistent lower limit of osmolality of the serosal bathing medium beyond which short-circuit current would be unaffected by hypo-osmotic steps. However, as reported by others (Lewis et al 1985), a bladder bathed on the serosal side by a gluconate Ringer solution in which sodium gluconate concentration was reduced by 50 %, produced a current approximately equal to that generated by the same bladder when bathed by a normal chloride Ringer solution. Hypo-osmotic steps in this diluted gluconate medium had little further effect on the SCC, indicating that a limit had been reached or passed.…”
Section: Methodsmentioning
confidence: 81%
“…If the sodium pump has a fixed flux ratio, sodium to potassium, then both the activation or recruitment of sodium pumps and the hyperpolarization of cells following a hypo-osmotic step would produce an increase in activity of cell potassium unless the basolateral membrane potassium conductance adjusted to match the changed uptake. Although specific evidence for changes in basolateral membrane conductance was not obtained in these studies, others (Schultz, 1981;Lewis et al 1985) have found a positive correlation between pump rate and basolateral membrane conductance.…”
Section: Second Mechanismmentioning
confidence: 82%
See 1 more Smart Citation
“…Another proposal regarding gluconate effects has been put forward by Lewis, Butt, Bowler, Leader & Macknight (1985). They found that gluconate reduces the Na+ permeability of the luminal membrane in toad bladder epithelium.…”
Section: Cl-pathwaysmentioning
confidence: 99%
“…Membrane chloride conductance is an essential feature of cellplar models for chloride transport across the cornea (1), trachea (2), and thick ascending limb of Henle's loop (3) and is thought to be an important regulatory site for fluid secretion and cell-volume regulation in some cells (4)(5)(6)(7). However, unlike sodium and potassium channels, which have been characterized using fluctuation analysis (8,9), little is known regarding anion permeability in most epithelia, and its constituent ion channels have not been identified (10).…”
mentioning
confidence: 99%